Safety and Efficacy of Ginkgo-Damole and Nitroglycerin or Sodium Nitroprusside on Hypertensive Cerebropathies: A Meta-Analysis. (4th September 2020) - Peng, Li; Zhao, Wei-kun; Xu, Tong-tong; Wu, Qi; Lu, Pan; Zhu, Pan-pan; Zheng, Xiao-ming
Abstract : Objective . To systematically evaluate the safety and efficacy of ginko-damole combined with nitroglycerin or unitary sodium nitroprusside on hypertensive cerebropathy. Methods . Four Chinese databases (VIP, CBM, Wanfang database, and CNKI database) and three English databases (Cochrane, PubMed, and EMBASE) were used to screen randomised controlled trials (RCTs) on treatments of hypertensive cerebropathy using both ginko-damole and nitroglycerin or unitary sodium nitroprusside. Outcomes included clinical effect, blood pressure after treatment, and adverse effects. These indicators were then analysed statistically using the RevMan 5.3 and Stata 12.0 software. Results . Altogether, 16 RCTs including 1507 patients with hypertensive cerebropathy were included in the present meta-analysis, of which, 755 patients treated with combined ginko-damole and nitroglycerin were included in the observation group and 752 patients treated with sodium nitroprusside were included in the control group. The curative effect of the observation group was significantly better than that of the control group (RR: 1.115 [1.077, 1.155], p < 0.05 ). DBPs of the observation and control groups were both lower after treatment, and no significant difference was observed between the observation and control groups (MD: −1.072 [−2.578, 0.434], p > 0.05 ). SBPs in the observation group were significantly lower than those in the control group (MD: −2.842 [−5.222, −0.462], p < 0.05 ). The probability of adverse response in both groups did not differ significantly (RR: 0.752 [0.412, 1.374], p > 0.05 ). Conclusion . Compared with sodium nitroprusside, the combined ginkgo-damole and nitroglycerin could better control blood pressure in patients with hypertensive cerebropathy and showed enhanced clinical effects and improved safety. However, due to poor quality of the included studies, results of the present meta-analysis should be confirmed by more stringent RCTs.